The impact of globalization on islamic education toward fiqh learning existence in covid-19 pandemic period - Firman Mansir (ATTARBIYAH: Journal of Islamic Culture and Education, 2020)
This research explains about the existence of Islamic Education in the middle of covid-19 pandemic that is currently struck the world, including Indonesia. This impact affects the learning process in schools and Madrasah. It is feared that the Covid-19 pandemic could undermine the existence of Islamic Education. The learning process of Islamic Religious Education is starting to be eliminated amid the siege of modern learning, thus, Islamic Education is in the spotlight because it is unable to compete in the midst of the pandemic. However, all these worries can fade because Islamic education is able to obtain these various entanglements and come back into existence with various learning models and methods used to offer the best for students in schools and madrasas